Prostate cancer - Ricardo Alonso Castillejos-Molina; Fernando Bernardo Gabilondo-Navarro (Instituto Nacional de Salud Pública, 2016)
Prostate cancer is the most frequent tumor found in men worldwide and in Mexico in particular. Age and family his- tory are the main risk factors. The diagnosis is made by prostate biopsy in patients with abnormalities detected in their prostate-specific antigen (PSA) levels or digital rectal exam (DRE). This article reviews screening and diagnostic methods as well as treatment options for patients diagnosed with prostate cancer. DOI: http://dx.doi.org/10.21149/spm.v58i2.7797